Where Is The Second Equation?

If a , b > 1 a,b>1 are integers satisfying 11 ( a 1 ) = 13 ( b 1 ) 11(a-1) = 13(b-1) , find the minimum value of a + b a+b .


The answer is 26.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Relevant wiki: Greatest Common Divisor

gcd ( 11 , 13 ) = 1 \gcd(11,13)=1 . 13 13 divides L.H.S and 11 11 divides R.H.S

a , b a,b must be of the form 13 n + 1 13n+1 and 11 m + 1 11m+1 respectively where n , m n,m are integers.

As a , b > 1 a,b>1 the minimum value of a a and b b occurs when n , m = 1 n,m=1 or a = 14 a=14 and b = 12 b=12 .

Hence minimum value of a + b = 14 + 12 = 26 a+b=14+12=\boxed{26} .

Moderator note:

Great work! I would have phrased it this way:

Let c = 11 ( a 1 ) = 13 ( b 1 ) c = 11(a-1) = 13(b-1) , then c c must be a multiple of 11 and 13. Since we want to minimize a , b > 1 a,b> 1 , then this suggests that should minimize c c as well. the minimum value of c c must be a multiple of 11 and 13. So a possible value of c c is 11 × 13 = 143 11\times13=143 . Hence, 143 = 11 ( a 1 ) = 13 ( b 1 ) a = 143 11 + 1 = 14 , b = 143 13 + 1 = 12 143 = 11(a-1) = 13(b-1) \Rightarrow a = \dfrac{143}{11} + 1 = 14 , b = \dfrac{143}{13} + 1 = 12 . The result follows.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...